Strategi Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kabupaten Muko-Muko, Bengkulu - Yenita Ekasari; Reflis Reflis; Satria Putra Utama; Dwi Maryani; Essy Anesta Asdami; Ranti Uchera (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Reducing the area of agricultural areas, especially paddy fields into palm oil plantations in the use of space in Mukomuko Regency, has raised concerns about the impact of these changes, namely the decline in rice productivity, which if allowed to drag on could lead to food insecurity due to the decreasing number of functional paddy fields. into oil palm plantations, especially in areas that are designated as agropolitan in the Mukomuko Regency spatial planning. Time and Place of Research: Research was conducted from October to November 2023 in Muko-Muko Regency, Bengkulu Province. To find out the strategy for managing land conversion, SWOT analysis is used. The results of the research show that the position of controlling the conversion of wetland agricultural land is in quadrant I, namely the position with an aggressive strategy (S-O). In this case the recommended strategy is to utilize strengths to take advantage of existing opportunities. Alternative strategies that can be implemented by policy makers, in this case the Mukomuko district government, to prevent the conversion of rice land to oil palm are clear regulations and establishing clear rice field zones in spatial plans, improving government policies in the farming sector, improving institutions in the farming sector, empowerment and socialization regarding land conversion regulations and improving agricultural facilities and infrastructure